HORSE AND HORSE-RELATED EQUIPMENT IN OKS CIVILIZATION - Jalilov Doston Muhiddin ugli (Innovate Conferences, 2025)
This article analyzes the occurrence of horses and horse-related equipment characteristic of nomadic pastoral communities from the Eurasian steppes within the territory of the Oxus civilization. The study examines how these objects were incorporated into cultural life and elucidates their functional and symbolic significance. Additionally, the article demonstrates the role of this phenomenon in the process of cultural interactions between the southern oases and the northern steppes.
Keywords: Jarkutan, Gonur Cemetery, Dashli, Suvliq, horse burial, Swat Cemetery, headless interment.